TERMINOLOGY OF DAKWAH IN THE PERSPECTIVE OF THE QURAN - Qudus, Syah Ahmad (Proceeding International Seminar of Islamic Studies, 2023)
Today, many people carry out da'wah activities but not as called for by the Qur'an. This is due to not understanding the position of Islam as a perfect religion, preserved and guaranteed from every deviation, change and insertion. Therefore, the authors make this as a background in this research. This study used a literature study research method (library research). Da'wah in language is an invitation in the form of calling, begging or inviting. Da'wah according to the term is an activity that is carried out consciously by a person or group of Muslims in inviting or calling on a person or group of people to live according to Islamic teachings, namely carrying out Allah's commands and avoiding Allah's prohibitions which have been stated in the Qur'an and hadith to obtain pleasure in world and in the hereafter. Da'wah elements are components contained in every da'wah activity. These elements are da'i (proselytizers), mad'u (preaching partners), maddah (preaching materials), wasilah (preaching media), thariqoh (preaching methods), and atsar (preaching effects).